SETTLEMENT OF FIDUCIARY CRIMES THROUGH RESTORATIVE JUSTICE APPROACH - Yusuf, Nawin; Kasim, Nur M.; Imran, Suwitno Yutye (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
The objective of this study is to examine the use of the restorative justice strategy in dealing with cases involving the transfer of fiduciary objects at the Gorontalo Police Station. This strategy is deemed more appropriate for resolving issues between creditors and debtors due to its focus on peaceful resolution that stresses deliberation and mutually advantageous solutions. This study employs empirical legal methodologies with a sociological juridical approach, together with qualitative tactics, to analyze data. The data was acquired via interviews conducted with police officers and fiduciary criminals who were implicated in multiple cases that took place in Gorontalo.The findings demonstrated the efficacy of the restorative justice strategy in mitigating conflict and expediting dispute settlement, circumventing the need for protracted and onerous legal proceedings. This strategy provides the debtor with the chance to rectify errors without being subjected to formal criminal penalties, while ensuring that the creditor receives the required recompense. However, the implementation of restorative justice encounters some challenges, particularly the limited comprehension of law enforcement personnel regarding this idea and the absence of comprehensive legislation governing the process of criminal mediation in cases involving financial crimes. Certain police officers remain unwilling to exercise the discretion granted to them due to concerns about breaching protocols or creating unfavorable perceptions within the community. In order to surmount these challenges, it is imperative to enhance the proficiency of the police force by providing more rigorous training and fostering better social integration. Additionally, it is crucial to review and amend the current rules, particularly Law No. 42 of 1999 pertaining to fiduciary security. This amendment should incorporate more explicit and thorough provisions pertaining to penal mediation as a viable alternative for settling fiduciary criminal cases. As regulation improves and law enforcement personnel have a better understanding, the implementation of restorative justice is anticipated to operate more efficiently, ensuring legal clarity and achieving a fairer outcome for all parties involved.